Building Evaluation Capacity within an Agricultural NGO using SWOT Analysis - Kathleen D. Kelsey (Journal of International Agricultural and Extension Education, 2018)
Evaluation capacity building (ECB) aims to create a learning organization committed to increasing evaluation knowledge and skills among employees (Fitzpatrick, Sanders, & Worthen, 2011). ECB framework was used to determine the scope of monitoring and evaluation activities within an international agricultural non-governmental organization (NGO) usinga strengths, weaknesses, opportunities, and threats analyses (SWOT). The objectives were to analyze current practices, capacity for evaluation activity at the project and organizational level, and propose a model for building evaluation capacity within the NGO. Existing documents and artifacts were content analyzed (Krippendorff, 2004) and 44 NGO employees, donor agency representatives, and similar NGO representatives were interviewed regarding their evaluation practices. Results indicated that project-level evaluation staff had sufficient training and expertise to conduct evaluation within the scope of their projects (strength). However, ECB and organizational learning from evaluation efforts were not institutionalized (weakness). The NGO lacked evaluationexpertise and leadership at headquarters level due to staff attrition and lacked technology to capture data for aggregation purposes to report on progress made toward mission between projects and over time (threat). Opportunities included promoting an Evaluation Specialist to lead efforts by recruiting from within the NGO and advancing the individual’s knowledge and skills through pursuit of a doctoral degree in evaluation. The NGO is advised to adopt a knowledge management system to capture and aggregate data between projects and over time to communicate better overall mission accomplishments to stakeholders and donors
Keywords: evaluation capacity building; international agricultural development monitoring and evaluation